Pengembangan Media Permainan Ular Tangga Pada Materi Keberagaman Budaya Indonesia Pelajaran IPAS Siswa Kelas IV - Leles Taria; Diana Pramesti; Rifki Hanif Setiawan (STKIP Subang, 2025)
This research is motivated by the monotonous nature of IPAS learning, which still heavily relies on textbooks and lecture-based methods, as well as the limited use of educational media, particularly game-based media, to support education, especially for the topic of Indonesian cultural diversity. The purpose of this study is to develop a Snakes and Ladders game as a learning medium on the topic of Indonesian cultural diversity in the IPAS subject for Grade IV students that is valid, practical, and effective. This research adopts a Research and Development (R&D) approach using the ADDIE development model. The research subjects consisted of 20 fourth-grade students. Data collection techniques included interviews, questionnaires, and tests. The data were analyzed using both quantitative and qualitative methods. Practicality data were obtained from student response questionnaires, while effectiveness data were derived from the analysis of pretest and posttest scores. The results showed that the media expert validation score was 84% (Very Valid), while both material experts gave a validation score of 80% (Very Valid). In terms of practicality, the small-scale trial yielded 95% (Very Practical), and the large-scale trial yielded 97% (Very Practical). The average pretest score was 39.13%, and the posttest score was 82.25%. The product's effectiveness, based on the N-Gain test, was 0.70 (High category), with an N-Gain percentage of 70.17%, which falls into the